Debunking a myth: plant consciousness - Mallatt, Jon M.; Blatt, Michael R.; Draguhn, Andreas; Robinson, David G.; Taiz, Lincoln (Protoplasma, 2021)
Claims that plants have conscious experiences have increased in recent years and have received wide coverage, from the popular media to scientific journals. Such claims are misleading and have the potential to misdirect funding and governmental policy decisions. After defining basic, primary consciousness, we provide new arguments against 12 core claims made by the proponents of plant consciousness. Three important new conclusions of our study are (1) plants have not been shown to perform the proactive, anticipatory behaviors associated with consciousness, but only to sense and follow stimulus trails reactively; (2) electrophysiological signaling in plants serves immediate physiological functions rather than integrative-information processing as in nervous systems of animals, giving no indication of plant consciousness; (3) the controversial claim of classical Pavlovian learning in plants, even if correct, is irrelevant because this type of learning does not require consciousness. Finally, we present our own hypothesis, based on two logical assumptions, concerning which organisms possess consciousness. Our first assumption is that affective (emotional) consciousness is marked by an advanced capacity for operant learning about rewards and punishments. Our second assumption is that image-based conscious experience is marked by demonstrably mapped representations of the external environment within the body. Certain animals fit both of these criteria, but plants fit neither. We conclude that claims for plant consciousness are highly speculative and lack sound scientific support.